2014
DOI: 10.1111/jgh.12391
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt in combination with or without variceal embolization for the prevention of variceal rebleeding: A meta‐analysis

Abstract: Adjunctive variceal embolization during TIPS procedures might be beneficial in the prevention of variceal rebleeding. However, given the heterogeneity of type of stents, embolic agents, type of varices, and indications of variceal embolization among studies, additional well-designed randomized, controlled trials with larger sample size and use of covered stents should be warranted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 41 publications
1
53
0
2
Order By: Relevance
“…Another meta‐analysis by Qi et al evaluated the use of variceal embolization in combination with TIPS. This analysis included studies that compared variceal embolization alone versus TIPS plus variceal embolization and demonstrated that combination therapy was associated with a significantly lower incidence of variceal rebleeding but a similar incidence of shunt dysfunction, encephalopathy, and death.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta‐analysis by Qi et al evaluated the use of variceal embolization in combination with TIPS. This analysis included studies that compared variceal embolization alone versus TIPS plus variceal embolization and demonstrated that combination therapy was associated with a significantly lower incidence of variceal rebleeding but a similar incidence of shunt dysfunction, encephalopathy, and death.…”
Section: Discussionmentioning
confidence: 99%
“…A number of meta-analyses have examined endoscopic therapies, b-blockers, and transjugular intrahepatic portosystemic shunts with respect to control of variceal bleeding and re-bleeding [22][23][24][25]. However, few meta-analyses have compared vasoactive medications used for the management of acute variceal bleeding [12,[26][27][28], and to our knowledge none have evaluated the efficacy of vasoactive drugs on preventing re-bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…At our knowledge, no other studies showed such data. This could be explained by the fact that oesophageal or gastric post-TIPS varices create a competitive flow, leading to more risk of stent thrombosis or stenosis because of lower flow into the TIPS (38,39). Indeed, persistent flow into varices can be responsible for hemodynamic steal from the PV leading to slower flow into the TIPS shunt and potentially higher risk of in-stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%